The design of fuzzy expert system implementation for analyzing transmissible disease of human - Fauzi; Huda M.; Teh K.S.M.; Haroon Z.; Ripin M.N.; Hehsan A.; Abas H.; Hehsan M.R.; Irawan J.; Abadi S.; Maseleno A. (Advanced Scientific Research, 2024)
Indexed by Scopus